Approaches For Enhancing Nurses' Well-Being And Mental Health (Journal of Namibian Studies : History Politics Culture, 2022)
The research explores strategies to improve the mental health and well-being of nurses, a population facing high levels of psychological distress and occupational exhaustion. It emphasizes the role of peer support in facilitating recovery, self-empowerment, and individual development. Peer support promotes a wellness paradigm by fostering a sense of community, understanding, and mutual assistance among nurses who have experienced similar experiences. However, peer support workers face stress, role ambiguity, boundary disputes, power differentials, and power ambiguity, which must be addressed through ongoing education and support. The study also highlights the importance of all-encompassing interventions, including mindfulness-based interventions, yoga, and relaxation techniques, in mitigating mental anxiety, exhaustion, and stress in the healthcare profession. Organizational solutions such as burden reduction, increased autonomy, and career development are also recommended. The research contributes to the growing focus on improving the mental and physical health of healthcare professionals, aligning with the United Nations' goal of prioritizing the well-being of this population. Healthcare systems can help nurses deliver better care, improve patient outcomes, and ensure the long-term viability of the nursing profession through evidence-based interventions and strategies.